2021
DOI: 10.14202/vetworld.2021.1901-1907
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of sitagliptin and losartan against fipronil-induced hepatotoxicity in rats

Abstract: Background and Aim: Fipronil (FPN) is a potent pesticide that is heavily used around the world in agriculture. However, its irrational use could potentially have deleterious effects on animals and humans. The present study aimed to investigate the ability of sitagliptin (Sit) and losartan (LOS), when used both individually or concurrently, to guard rat liver against the acute hepatotoxicity caused by FPN. Materials and Methods: Forty-two adult male Wistar rats were equally divided into seven groups (6/group).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…QR (3,3′,4′,5,7-pentahydroxyflavone) is a ubiquitously present polyphenolic flavonoid in plant food sources such as fruits, vegetables, tea, aromatic plants, and red wine . QR usage has been reported to have the therapeutic potential to mitigate various kinds of toxicity, such as cardiotoxicity, nephrotoxicity, neurotoxicity, and hepatotoxicity. Studies have reported that mitochondrial dysfunction in rodents can be modulated by pretreatment with QR, and the rationale behind its ameliorative effect on mitochondrial toxicity is based on its antioxidant properties. , Due to the scarcity of literature on TNP-mediated hepatotoxicity in the mitochondria, it is still not clear what role the mitochondria play in triggering the chain of events that eventually lead to subcellular toxicity. Hence, the present study was aimed at mounting the therapeutic aspects of QR to control the hepatotoxic properties of TNP exposure in isolated rat liver mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…QR (3,3′,4′,5,7-pentahydroxyflavone) is a ubiquitously present polyphenolic flavonoid in plant food sources such as fruits, vegetables, tea, aromatic plants, and red wine . QR usage has been reported to have the therapeutic potential to mitigate various kinds of toxicity, such as cardiotoxicity, nephrotoxicity, neurotoxicity, and hepatotoxicity. Studies have reported that mitochondrial dysfunction in rodents can be modulated by pretreatment with QR, and the rationale behind its ameliorative effect on mitochondrial toxicity is based on its antioxidant properties. , Due to the scarcity of literature on TNP-mediated hepatotoxicity in the mitochondria, it is still not clear what role the mitochondria play in triggering the chain of events that eventually lead to subcellular toxicity. Hence, the present study was aimed at mounting the therapeutic aspects of QR to control the hepatotoxic properties of TNP exposure in isolated rat liver mitochondria.…”
Section: Introductionmentioning
confidence: 99%